Pelatihan Menggunakan Microsoft Excel Untuk Membantu Peserta Didik Dalam Menyelesaikan Masalah Bangun Datar Fase D Di Mts Negeri 7 Desa Kuntu - Agus Dahlia; Rahma Qudsi; Neneng Purnamawati; Bagus Prasetio; Putri Rahmatillah (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Information technology is inseparable in the development of education, technology can be used as a tool or media to realize the goals of learning. Information technology is also useful as a stimulation of learning so that students can construct their own knowledge through various activities such as: problem solving, reasoning, and communicating (doing math), as a vehicle for training critical and creative thinking. At MTs Negeri 7 Kuntu Village, the utilization of Information Technology has not been done optimally in the process of teaching and learning activities. Information Technology such as Microsoft Excel is needed as additional information on learning technology in the era of the Industrial Revolution 5.0 for teachers and students at MTs. Microsoft Excel can be used as an alternative solution for learning Flat Shapes Mathematics. The Community Service Team aims to conduct training in the use of Microsoft Excel to help students solve math problems in flat shapes. The implementation method in this community service goes through three stages, namely the preparation, implementation and evaluation stages. The results obtained from this community service show that students' understanding of the use of Microsoft Excel in solving phase D flat shapes problems has increased and also increased students' interest and motivation in learning math.